PENYELEWENGAN HAK ATAS KEKAYAAN INTELEKTUAL DALAM PERJANJIAN LISENSI MEREK - Sabila, Berliana Alsa; Exaudi Bakara, Dustin Orlando (Jurnal Aktual Justice, 2023)
Brand license agreements are misused in business operations involving intellectual property. This study aims to examine the implications of brand license agreement misuse in business practices related to intellectual property rights. The outcome of this study demonstrates the necessity for brand licensing agreement protection in business practices in intellectual rights to stop brand license agreement abuse. An invalid brand license agreement will have an adverse effect on all parties. This study explains efforts to resolve disputes in brand license agreements in accordance with Article 84 of Act No. 15 of 2001 Concerning Brand Matters.